Legal Uncertainty in Coastal Area Regulation: Its Impact on Economic Rights of Tourism Actors in Bangka Belitung - Yournawan, Hendra; Hariansah, Syafri (Dinasti Research, 2025)
Legal uncertainty in coastal regulation in Bangka Belitung has caused multidimensional impacts, particularly on the economic rights of tourism actors and the protection of coastal communities’ environmental rights. This study aims to examine how the lack of harmonization between national and regional regulations especially concerning zoning plans and mining permits creates conflicts of authority and undermines legal protection for tourism-based livelihoods. Using a normative-empirical legal research method, this research integrates doctrinal analysis of statutory regulations with a socio-legal approach to understand the lived experiences of affected stakeholders. Data were obtained through document review, field observations, and in-depth interviews with tourism operators, community members, and environmental advocates. The study finds that the inconsistency between regional zoning (RZWP3K) and centrally issued mining permits (WIUP) has enabled illegal mining in tourism zones, causing severe environmental degradation and diminishing tourism investment interest. This situation has led to income loss, social tensions, and the criminalization of environmental defenders. The study concludes that legal ambiguity does not only threaten environmental sustainability but also violates constitutional guarantees to a healthy environment and decent livelihood. Harmonization of central and regional policies, strengthening of institutional enforcement mechanisms, and inclusive community participation are essential to ensure that the law effectively supports environmental justice and economic resilience in coastal areas.